Analysis of the asynchronous dental teleconsulting of Telehealth Brazil Networks in Minas Gerais - Lígia Cristelli Paixão; Vanessa Andrade Costa; Efigênia Ferreira e Ferreira; Antônio Paulino Ribeiro Sobrinho; Renata de Castro Martins (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract: This cross-sectional study aimed to evaluate the asynchronous dental teleconsulting of Telehealth Brazil Networks Program in Minas Gerais. Data were collected from secondary databases of the Clinical Hospital of the Universidade Federal de Minas Gerais (CH/UFMG) and Medical School of UFMG (MS/UFMG), from July 2015 to July 2017. The variables analyzed were telehealth center, sex and profession, date and time questions and answers, response time in days, whether the issue was duly addressed, whether the teleconsulting was attended, post status, professional's satisfaction, conduct adopted after teleconsulting, dental specialty area, and type of issues. Sociodemographic data from the Intermediate Geographical Regions (IGR) of Minas Gerais, including the Municipal Human Development Index (MHDI) and Gini Index were also collected. The results were analyzed using SPSS v.22.0. In total, 3,920 teleconsulting were recorded, with increasing demand in the study period. Most were requested by dentists (93.3%) and female professionals (78.6%), during office hours (78.6%), and related to general conducts (72.1%). Almost all were attended (99.7%), with a maximum response time of two days (75.0%). A low feedback on satisfaction and resolution of issues (missing data of 57.2% and 70.2%, respectively) was recorded. Only 5.2% had information on whether patients were referred. The most common inquires were of issues about Pathology/Stomatology specialties (19.0%) and Pharmacology/Anesthesiology (18.8%). The response occurred within the expected time, with prevalent issues in basic dental areas and general conducts. Feedback from professionals must be encouraged to allow a better analysis and improvements of the program.